Discrete noise approximation of axial compressor and centrifugal fans - A P Alekseev (RUDN Journal of Engineering Researches, 2009)
Equations for discrete noise approximation of axial compressor and centrifugal fans depending upon number of geometrical and operating parameters are obtained.